SISTEM INFORMASI BERBASIS WEB PADA PERSEWAAN BUKU GRAMAS - Mentari M, Helda; Murti, Hari (Information Technology and Telematics, 2018)
Abstract Gramas book rental is a business in the lending of books covering comics and novels. Currently the process undertaken in the lease of the book Gramas has been using the computer but still found obstacles that members dissatisfaction in the process of booking and leasing books. This research aims to create a web-based book rental information system on Gramas book rental which can facilitate member to get information about book rental and ordering online. System development method used is waterfall, system and software design using UML, implementation using PHP and MySQL. This research resulted in a book rental system on Gramas book rentals that gave advantages of facilitating the delivery of information, improving services, and increasing the interest of members to rent books so as to increase revenue.